2021
DOI: 10.21203/rs.3.rs-569798/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical Frailty Scale (CFS) Indicated Frailty is Associated with Increased In-Hospital and 30-Day Mortality in COVID-19 Patients: A Systematic Review and Meta-Analysis

Abstract: Background: The concept of frailty provides an age-independent, easy-to-use tool for risk stratification. We aimed to summarize the evidence regarding the use of frailty tools in COVID-19, assessing the risk of frail patients for in-hospital and 30-day mortality, intensive care unit (ICU) admission, and length of hospitalization (LOH).Methods: The protocol was prospectively registered via PROSPERO (CRD42021241544). Studies reporting on frailty in COVID-19 patients were eligible. We compared in-hospital and 30-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…As the pandemic advances, other investigations on the associations of frailty, organ support, and long-term survival in critically ill patients with COVID-19 might provide new insights. However, recent systematic reviews studying frailty in hospitalized COVID-19 patients demonstrated that all reports concern databases from 2020, similar to ours (3, 27). And the association of the concept of frailty with ICU outcomes has been demonstrated before COVID-19 (23), highlighting that it is not specific to this infectious disease.…”
Section: Discussionsupporting
confidence: 86%
“…As the pandemic advances, other investigations on the associations of frailty, organ support, and long-term survival in critically ill patients with COVID-19 might provide new insights. However, recent systematic reviews studying frailty in hospitalized COVID-19 patients demonstrated that all reports concern databases from 2020, similar to ours (3, 27). And the association of the concept of frailty with ICU outcomes has been demonstrated before COVID-19 (23), highlighting that it is not specific to this infectious disease.…”
Section: Discussionsupporting
confidence: 86%